Stone‐Induced Purulent Choledocoduodenal Fistula Presenting with Ascending Cholangitis. Issue 1 (2018) - Shams, Christienne; Cannon, Michael; Bortman, Jared; Hakim, Seifeldin
ABSTRACT : N/A: A biliary enteric fistula (BEF) is a rare, abnormal communication between any segment of the biliary tree with any portion of the small or large intestine. BEF is more frequently diagnosed with the increasingly widespread use of endoscopic retrograde cholangiopancreatography. Different theories have been postulated regarding the etiology of this fistula formation, with the most likely cause being gallstones. Treatment modalities, ranging from conservative management to surgical reconstruction, show varying levels of success. We present a case of BEF secondary to large common bile duct stones, successfully treated with endoscopic sphincterotomy (EST) followed by papillary balloon dilatation, and we briefly discuss large stone retrieval in the setting of atypical anatomy.